METHODOLOGY FOR TEACHING INFORMATICS AND INFORMATION TECHNOLOGY SCIENCE USING THE DISTANCE LEARNING PLATFORM ISPRING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article focuses on the issues of the use of advanced pedagogical technologies in the education of student youth from the visual arts, one of the important disciplines that fall into the aesthetic cycle. It also tells about the importance of Information Technology in obtaining independent knowledge, the fact that the preparation and transmission of resources corresponding to the worldview of young people in information technologies in a modern way, in an interactive and creative way consists of current issues today.